Prisoners of the past [videorecording] - Dormer, Mike; Fairley, John; Hughes, Gruyneth; Marshall, Jill; Welfare, Simon (Red Empire presented by Robert Conquest ; series producer, Guyneth Hughes, 1990)
Covers the communist leadership of Breznew, Andropov and Konstantin Chernenko and Michael Gorbachev. Also deals on the KGB KOMSOMOL of the Communist Party of the Soviet Union.